PENGARUH GAYA KEPEMIMPINAN DAN FASILITAS TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. KENCANA ANDALAN NUSANTARA - Melisa Melisa; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
PT. Kencana Andalan Nusanatara is one of the companies engaged in the development of oil palm. For the office of PT. Kencana Andalan Nusantara Medan itself is located on Jalan Cemara No.3, Medan. PT. Kencana Andalan Nusantara Medan also has 42 employees. Decreased employee productivity causes employees to be unable to work effectively and efficiently in providing optimal work results to the company. Superiors are considered unable to make good decisions when needed by their subordinates and make subordinates have to spend time waiting for directions from superiors. Strict supervision and care in order to make employee expenses efficient makes it difficult for employees to work. This research uses quantitative descriptive research. The total population in the study was 42 employees with a sampling technique using a saturated sample. Simultaneously there is a significant influence between the variables of leadership style and facilities on the work productivity of employees of PT. Kencana Andalan Nusantara. While partially found leadership style variables have a significant effect on the work productivity of employees of PT. Kencana Andalan Nusantara. Partially it was found that the facility variable had a significant effect on the work productivity of PT. Kencana Andalan Nusantara. The results of this study indicate that the facility variable has more influence than the leadership style on the work productivity of PT. Kencana Andalan Nusantara.